Effectiveness of Quercetin in Kenikir Leaves (Cosmos Caudatus Kunt) in Nanoemulsion Formulas with VCO (Virgin Coconut Oil) and Olive Oil Phase - Hajir, Siti; Nugrahani, Ratri Ariatmi; Ismiyati, Ismiyati (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
Kenikir (Cosmos Caudatus Kunth) is a herbal plant and contain quercetin compounds (flavonoids) which can have an effect as an antioxidant, antibacterial, antifungal, anti-inflammatory. This study aims to determine the effect of adding quercetin extract to a nanoemulsion formula with several oil phases, namely VCO (Virgin Coconut Oil) and Olive Oil. Evaluation of the characteristics of the preparation for each formula included organoleptic test, pH test, particle size, emulsion type, and determination of the level of quercetin absorbed in the nanoemulsion system as well as antioxidant activity test using the DPPH (1,1-diphenyl-2-picrylhydrazil) method. The results showed that the nanoemulsion preparations with the VCO oil phase, olives had good and stable characteristics. The pH test of the nanoemulsion was in the range of 4.5-6.5 while for the emulsion type it was an Oil in Water (M/A) type and the particle size was in accordance with the criteria for nanoemulsion preparations <200 nm, namely 13-178 nm. To see the ability of the active substance to be absorbed in the formula by calculating the % EE (Entrapping Efficiency) the % EE is obtained, which is 99%, which means that the nanoemulsion formula is able to absorb the active substance well and the antioxidant activity test using the DPPH method shows in the formulation of kenikir extract with the VCO oil phase gives an IC50 value of 52.238 ppm while the olive oil phase is 305.783 so that the nanoemulsion formula with the VCO oil phase is more reactive than the olive oil phase.